PENGAJARAN SAINS DENGAN PRAKTIKUM LABORATORIUM: PERSPEKTIF DARI GURU-GURU SAINS SMPN DI KOTA CIMAHI - Sumintono, Mr Bambang; Ibrahim, Mohd Ali; Phang, Fatin Aliah (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 2010)
Science laboratory activities are important part of science learning at school level. However there are still debate about how we put in the context of science learning and best approach to use them. Using mixed methods, this research investigates science teachersâ perspectives regarding science laboratory activities in Cimahi, West Java, Indonesia at public junior secondary school level. There were sixty two teachers participated giving their answer and write their comments in the questionnaire, then followed with informal discussion. Some findings revealed: teachers view that laboratory work is to make students finding science facts and principle, their difficulty to conduct the activity which related to support needed, they require specific training about laboratoryâ skills and management and their identification of science teachers preparation and competency.Keywords: science education, laboratory work, science in junior secondary school